Correlation between thyroid fine needle aspiration and pathological examination: a 10 year retrospective study - Rodrigo Ribeiro e Silva; Vinicius Ribas de Abreu Borges; Alexandre Grunfeld Starling Jardim; Maria Luisa Hostin Volpi; Leonora Zozula Blind Pope; Manuella Zattar Medeiros (Einstein (São Paulo), 2023)
ABSTRACT Objective To establish the diagnostic performance of fine-needle aspiration in detecting benign and malignant neoplasm in comparison with post-thyroidectomy histopathological findings among patients who received a thyroidectomy. Methods Retrospective observational data collected between 2011–2021 were included from patients who received partial or total thyroidectomy. The Bethesda system was used to classify neoplasms from fine-needle aspiration procedures as benign or malignant. Sample characteristics, diagnostic accuracy, sensitivity, specificity, and predictive values were evaluated. Results Patients (n=360) who underwent thyroidectomy were analyzed, of whom 142 (39.4%) and 218 (60.6%) had benign and malignant neoplasms, respectively. Using the Bethesda system, 23 (6.4%) were classified as unsatisfactory result (BI), 83 (23.1%) as benign (BII), 50 (13.9%) as atypia of undetermined significance (BIII), 23 (6.4%) as suspected follicular or Hürthle cell neoplasia (BIV), 102 (28.3%) as suspected malignancy (BV) and 79 (21.9%) as malignant (BVI). The fine-needle aspiration diagnostic accuracy for carcinomas was 92%, while the sensitivity and specificity were 94.4% and 86.9%, respectively. The negative and positive predictive values were 87.9% and 93.9%, respectively. Conclusion Fine-needle aspiration has high diagnostic accuracy, sensitivity and specificity, and is a reliable test for distinguishing between benign and malignant thyroid pathologies.